Conformational Change of Tetratricopeptide Repeats Region Triggers Activation of Phytochrome-Associated Protein Phosphatase 5 - von Horsten, Silke; Essen, Lars-Oliver (Frontiers in Plant Science, 2021)
Phytochrome activity is not only controlled by light but also by post-translational modifications, e. g. phosphorylation. One of the phosphatases responsible for plant phytochrome dephosphorylation and thereby increased activity is the phytochrome-associated protein phosphatase 5 (PAPP5). We show that PAPP5 recognizes phospho-site mimicking mutants of phytochrome B, when being activated by arachidonic acid (AA). Addition of AA to PAPP5 decreases the α-helical content as tracked by CD-spectroscopy. These changes correspond to conformational changes of the regulatory tetratricopeptide repeats (TPR) region as shown by mapping data from hydrogen deuterium exchange mass spectrometry onto a 3.0 Å crystal structure of PAPP5. Surprisingly, parts of the linker between the TPR and PP2A domains and of the so-called C-terminal inhibitory motif exhibit reduced deuterium uptake upon AA-binding. Molecular dynamics analyses of PAPP5 complexed to a phyB phosphopeptide show that this C-terminal motif remains associated with the TPR region in the substrate bound state, suggesting that this motif merely serves for restricting the orientations of the TPR region relative to the catalytic PP2A domain. Given the high similarity to mammalian PP5 these data from a plant ortholog show that the activation mode of these PPP-type protein phosphatases is highly conserved.